Empowerment of Community Broad-Base Education Center for Arabic-Jawi Study at Deah Nurul Yaqin - *Nuriman Abdullah; Syarifah Rahmah (Riwayat: Educational Journal of History and Humanities, 2022)
Broad-based reinforcement community education in the process of managing Arabic-Jawi recitation institutions through mapping problems encountered on deah Nurul Yaqin, Darul Ihsan District, East Aceh Regency. The development of the study center aims to strengthen managerial and administrative governance in the Islamic religious learning process. Participatory action research (PAR) has been used to deal with related issues. The mentoring program has added to both managerial and administrative governance measurable and structured. Assistance and strengthening of administrative and managerial governance have had an impact increase the capacity of Arabic-Jawi learning. Another positive impact of mentoring has increased managerial ability, learning process for teachers, and administrative management making hall Arabic-Jawi recitation competitive in system learning, managerial and governance administration.